2021
DOI: 10.3390/ijerph18136875
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Worries among Pregnant Women during the COVID-19 Pandemic: A Multilevel Analysis

Abstract: Background. Several studies have identified pregnant women as a vulnerable group during the COVID-19 pandemic. The perinatal period has been identified as a stage of great risk for the mental health of pregnant women, due to a large increase in mental pathologies during this period. In this context, the objective of the present study was to assess the associations between socioeconomic and demographic factors, health concerns and health information management, and anxiety level during the COVID-19 pandemic in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
5

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 82 publications
(112 reference statements)
1
22
0
5
Order By: Relevance
“…Regarding COVID-19 exposures and symptoms, our results suggest that having symptoms and/or confirmed COVID-19 diagnosis were related to anxiety and PTSD only in pregnant women. These results can be explained by concerns about foetal health (Esteban-Gonzalo et al, 2021;Meraya et al, 2021;Mortazavi et al, 2021). In addition, experiencing the death of a close person due to COVID-19 was related to anxiety and depression in postpartum women but not in pregnant women and to PTSD symptoms in both pregnant and postpartum women.…”
Section: Discussionmentioning
confidence: 82%
“…Regarding COVID-19 exposures and symptoms, our results suggest that having symptoms and/or confirmed COVID-19 diagnosis were related to anxiety and PTSD only in pregnant women. These results can be explained by concerns about foetal health (Esteban-Gonzalo et al, 2021;Meraya et al, 2021;Mortazavi et al, 2021). In addition, experiencing the death of a close person due to COVID-19 was related to anxiety and depression in postpartum women but not in pregnant women and to PTSD symptoms in both pregnant and postpartum women.…”
Section: Discussionmentioning
confidence: 82%
“…Women also mentioned the lack of updates and information from the hospital on the risk of COVID-19 in pregnancy, COVID-19 symptoms and complications, and available health services, hence they had to be proactive in information seeking [40] , [43] , [52] , [54] , [55] , [56] . According to Estaban-Gonzalo et al’s study [61] , women with higher satisfaction levels with the information provided by healthcare professionals and a greater degree of information about COVID-19 restrictions, symptoms, and complications had a lower state anxiety score, whereas lack of information on restrictive measures was associated with higher state anxiety scores.…”
Section: Resultsmentioning
confidence: 99%
“…In Liu’s study [70] , 45.8% of mothers did not have a support person during birth, and another study [49] found lower birth satisfaction in mothers who did not have a birth support partner than those who had. Qualitative findings often reported negative experiences of mothers who did not have a support partner present during labour [30] , [36] , [39] , [45] , [46] , [61] , [66] , [68] , [87] . Some mothers perceived the absence of a birth partner as a loss of reassurance and advocate [55] , [78] while others felt alone, stressed, anxious, and that their mental health was at stake [44] , [45] , [52] , [65] .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, investigations have shown women to be a vulnerable group during the COVID-19 pandemic. This worry is even more among pregnant women who occasionally experience pregnancy and postpartum mental illnesses (depression, anxiety and postpartum psychosis), resulting in bipolar disorder 17. These situations are a cause for concern in Somalia, whose women of reproductive age represent 38% of the household, with a worrying maternal mortality rate of 692 18.…”
Section: Introductionmentioning
confidence: 99%